2022
DOI: 10.1371/journal.pone.0261978
|View full text |Cite
|
Sign up to set email alerts
|

Discriminatory attitude towards people living with HIV/AIDS and its associated factors among adult population in 15 sub-Saharan African nations

Abstract: Background Discrimination of people living with HIV/AIDS is one of the reported obstacles to the achievement of universal access to HIV/AIDS prevention, treatment, care, and support programs. Many international agencies have made combating HIV/AIDS stigma and discrimination a top priority. However, previous evidence in different parts of Africa revealed that the magnitude of HIV/AIDS-related discriminatory attitude is significantly high. Objective To assess discriminatory attitude towards people living with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
11
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 24 publications
16
11
3
Order By: Relevance
“…We also discovered that married Thai adults had more discriminatory attitude than those who had never married. This is similar to studies conducted in Ethiopia [49] and Nigeria [34], but contradicts studies conducted in sub-Saharan Africa [50], which found that married individuals have a lower discriminatory attitude toward PLWHA than singles. It is possible that those who had married had a more discriminatory attitude toward PLWHA because most married people are older and may have faced HIV/AIDS stigma through their experiences.…”
Section: Discussionsupporting
confidence: 80%
“…We also discovered that married Thai adults had more discriminatory attitude than those who had never married. This is similar to studies conducted in Ethiopia [49] and Nigeria [34], but contradicts studies conducted in sub-Saharan Africa [50], which found that married individuals have a lower discriminatory attitude toward PLWHA than singles. It is possible that those who had married had a more discriminatory attitude toward PLWHA because most married people are older and may have faced HIV/AIDS stigma through their experiences.…”
Section: Discussionsupporting
confidence: 80%
“…This finding aligns with a recently published study from an analysis of discriminatory attitudes in 15 sub-Saharan African nations using demographic and health survey data, which found that (a) young adults and individuals with (b) lower income and (c) lower education had higher odds of holding discriminatory attitudes toward PLHIV (Teshale & Tesema, 2022). Teshale and Tesema (2022) posit that the reason for the higher prevalence of discriminatory attitudes in younger populations could be attributed to younger adults relying on their parents for information related to HIV/AIDS rather than obtaining this information in a more formal setting, such as the workplace or in an educational setting. This theory may be supported by the results of the present study, as over half (55%) of those ages 15-25 have either no education (6%) or primary education (49%).…”
Section: Discussionsupporting
confidence: 91%
“…A study conducted by Teshale and Tesema[ 15 ] using the 15 Demographic and Health Survey data in Sub-Saharan Africa (SSA) from 2015 to 2019/20 with a total weighted study sample of 318,186 showed that the prevalence of discriminatory attitude towards HIV/AIDS in the 15 sub-Saharan African nations was 47.08% (95% CI: 47.08, 47.42).…”
Section: Discussionmentioning
confidence: 99%